Word Stress in Santri Utterance: A Comparative Analysis of Acoustic Phonetics - Salji; Al Farisi; Saleh (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
Although word stress in Arabic is not phonemic, proper use can minimize communication ambiguity. This study aims to analyze the production of word stress by students of Arabic as a second language (L2) and compare it with native speakers. This comparative study, involved six second-year students of Madrasah Aliyah as research samples. The research data were collected using listening, recording, and note-taking techniques. Then the research data were analyzed using Praat version 6.4.01 to find the stress accurately based on fundamental frequency, duration, and intensity level. The results showed that most L2 learners produced stress correctly on words with light syllables, but incorrectly on heavy and super heavy syllables. On the other hand, the form of word pronunciation also affects stress errors. Words characterized by super heavy syllables and a pause form are typically pronounced with weak stress. In addition, stress errors occur in syllables with double consonants where L2 learners do not apply good enough stress so that they sound like single consonants. These errors occur due to their mother tongue's different word stress systems. The findings are expected to positively impact L2 learners and teachers, by highlighting pronunciation issues, particularly concerning word stress.